Parthenocissus quinquefolia Virginia Creeper: FPS454/FP454, 6/2007 - Gilman, Edward (EDIS, 2007)
This document provides an overview of the Virginia creeper (Parthenocissus quinquefolia), a deciduous vine known for its rapid growth and attractive foliage. It details the plant’s characteristics, including its palmately divided leaflets that turn scarlet in the fall and its bluish-black berries. The document discusses the plant’s adaptability to various soil types and light conditions, its high drought tolerance, and its potential uses in landscaping. Additionally, it highlights the plant’s invasive potential and the need for careful management to prevent it from becoming weedy. The document also mentions the cultivar ‘Engelmanni’ and provides information on propagation and pest resistance. Original publication date October 1999.